Pengembangan Skill Digital Siswa SMK melalui Pemanfaatan Generatif AI - Rita Wahyuni Arifin; Ari Nurul Alfian; Sumardiono Sumardiono; Reykhando Rifki Awiliyanto (Jurnal Bhakti Karya dan Inovatif, 2025)
The enhancement of digital skills has become a key necessity in the technological era, especially for vocational high school (SMK) students in addressing the gap between curricula and industry demands. This community service activity focuses on utilizing Generative AI to support the development of students' digital skills through project-based training, adaptive learning, and pre-test and post-test evaluations. The results showed a significant improvement in students' understanding of Generative AI technology, with 61.9% of participants providing excellent feedback on the material. Students' interest and satisfaction levels were also high, confirming the training's relevance to industry needs. In conclusion, the use of Generative AI is an innovative solution to enhance SMK students' digital skills, bridge the gap between curricula and the workforce, and prepare them to face global challenges in the digital era. Keywords: Digital era, Generative AI, Digital skills, Competency development, Vocational High SchoolEra digital, Generatif AI, Keterampilan digital, Pengembangan kompetensi, SMK